Alginate-based diblock polymers: preparation, characterization and Ca-induced self-assembly. Issue 38 (17th September 2021) - Solberg, Amalie; Mo, Ingrid V.; Aachmann, Finn L.; Schatz, Christophe; Christensen, Bjørn E.
Abstract : Renewable resources can provide a range of different polysaccharide blocks that can be used to prepare new types of stimuli-responsive polysaccharide-based block copolymers. Abstract : Renewable resources can provide a range of different polysaccharide blocks that can be used to prepare new types of stimuli-responsive polysaccharide-based block copolymers. Alginates are natural polysaccharides widely used as biomaterials. Functional properties depend on the content and distribution of the two 4-linked monomers (β-d -mannuronate (M) and α-l -guluronate (G)). Blocks of l -guluronate (G n ) are responsible for cooperative binding of calcium ions and hydrogel formation. Incorporation of such blocks in block polysaccharide copolymers would represent a new class of engineered, Ca-sensitive biomacromolecules. Dioxyamines and dihydrazides have recently been shown to be well suited for preparation of block polysaccharide structures. Here we first show that when applied to alginate blocks (G n and M n ) the two types are both very reactive, but the detailed distribution of acyclic ( E )- and ( Z )-forms and cyclic N -pyranosides, reaction kinetics, conjugate stability, and the rate of Schiff base reduction with α-picoline borane differ considerably, also compared to other polysaccharides. Hence, alginate specific protocols were developed. The linkers introduce a highly flexible joint in otherwise semiflexible G n -based diblocks. This was demonstrated by SEC-MALS using a symmetrical G n - b -G n diblock, which in solution can best be described according to a broken rod model. Ca-Induced self-assembly of G n - b -dextran diblocks was studied by dynamic light scattering, demonstrating that well defined nanoparticles could be prepared for certain combinations of chain lengths. Taken together, this approach provides a new class of engineered, stimuli-responsive block polysaccharide copolymers solely based on natural resources.